Identification and Characterization of Mediators of Fluconazole Tolerance in Candida albicans - Delarze, Eric; Brandt, Ludivine; Trachsel, Emilie; Patxot, Marion; Pralong, Claire; Maranzano, Fabio; Chauvel, Murielle; Legrand, Mélanie; Znaidi, Sadri; Bougnoux, Marie-Elisabeth; d’Enfert, Christophe; Sanglard, Dominique (Frontiers in Microbiology, 2020)
Candida albicans is an important human pathogen and a major concern in intensive care units around the world. C. albicans infections are associated with a high mortality despite the use of antifungal treatments. One of the causes of therapeutic failures is the acquisition of antifungal resistance by mutations in the C. albicans genome. Fluconazole (FLC) is one of the most widely used antifungal and mechanisms of FLC resistance occurring by mutations have been extensively investigated. However, some clinical isolates are known to be able to survive at high FLC concentrations without acquiring resistance mutations, a phenotype known as tolerance. Mechanisms behind FLC tolerance are not well studied, mainly due to the lack of a proper way to identify and quantify tolerance in clinical isolates. We proposed here culture conditions to investigate FLC tolerance as well as an easy and efficient method to identity and quantify tolerance to FLC. The screening of C. albicans strain collections revealed that FLC tolerance is pH- and strain-dependent, suggesting the involvement of multiple mechanisms. Here, we addressed the identification of FLC tolerance mediators in C. albicans by an overexpression strategy focusing on 572 C. albicans genes. This strategy led to the identification of two transcription factors, CRZ1 and GZF3. CRZ1 is a C2H2-type transcription factor that is part of the calcineurin-dependent pathway in C. albicans, while GZF3 is a GATA-type transcription factor of unknown function in C. albicans. Overexpression of each gene resulted in an increase of FLC tolerance, however, only the deletion of CRZ1 in clinical FLC-tolerant strains consistently decreased their FLC tolerance. Transcription profiling of clinical isolates with variable levels of FLC tolerance confirmed a calcineurin-dependent signature in these isolates when exposed to FLC.